SISTEM MONITORING MOBIL RENTAL MENGGUNAKAN GPS TRACKER - Dedie Citra Mahendra; Teguh Susyanto; Sri Siswanti (Jurnal Ilmiah SINUS, 2018)
Currently car rental business is a business that promises many benefits. The number of car rental service customers each year is increasing, this is seen from the number of car rental businessmen increasingly from year to year. But behind the business profits are quite tempting there have been many complaints in the car rental business is the crime of theft. There have been many tools or ways taken to overcome the crime of car theft, but not many can be the right solution. Making this monitoring application aims to implement a GPS Tracking based security system in which the monitor can display the status and location of the existence of the car that has been hired.The method used is object-oriented software engineering including data types, data retrieval methods, system analysis, system design, system development, and testing. The end result of this research is a tool and monitoring application system capable of displaying icon maker according to the existence of the car and can display notification or alert. The tool used is Arduino Uno with some modules like GPS Module to capture coordinates and GPRS Module to send data to the database server.To view using the web with the monitoring map and alert system. Alert system will automatically process the data into the database, if the lease time exceeds the limit of rent then the alert will process the distance data between a rental car with garage. If the distance exceeds 4 km then the system will display alert/notification. Then the admin can also track the existence of the car. The functional test result of the system works well, the result of the validity test of the system provides valid data with 0.0002 tolerance average, and the result of the feasibility test of the system can be declared eligible for use.